Guide the Quran Recitation (Qira’at) by Al Khatib al Shirbiny in Surat al Baqarah (investigate and analytics study) - Almelhem, Munira Saud; Alshammri, Haia Hamdan (Journal of Islamic Sciences, 2020)
The research aimed to definition and impact of Quran Citation (Qira’at) Guide on explaining meaning of Quran’s Ayaat. The main objective is investigated Tafsir surat al Baqarah by al Khatib al Shirbini in his work “Al Siraj al Mounir fi al’iieanat ealaa maerifat baed maeani kalam rabana alhakim alkhabir” The main research objectives are: first investigates how he mentions the difference Qira’at in his Tafsir. Second, identified Qira’at effects from the meaning prospective on Tafsir. Furthermore, applying method of analytical induction. The research attracting words with difference recitation. Al Khatib al Shirbini, attributes all guides to Arabic language rules place, and guides some words without attribute in 44. Other ways, in 46 words there are supporting meaning (Tafsir).